From North Africa to Campania: Trade and local imitations of African Cooking Ware. An overview and new data from the North-Vesuvian territory - Castaldo, Vincenzo (Rei Cretariae Romanae Fautorum Acta, 2022)
The present contribution analyses the impact of the integration of African products on the western markets and its influence on the Roman economy. This study will focus the attention on the African Cooking Ware found in Campania and the distribution of this pottery class at the regional and sub-regional level. In fact, the analysis of pottery assemblages from several sites in the Bay of Naples and in the Vesuvian territory has highlighted the existence of a good system of exchange where factors such as roads, merchants and itinerant markets have played an important role. The archaeological evidence suggests that the presence of African Cooking Ware in the region and the prestige of this pottery class has subsequently favoured the emergence of local productions imitating African forms. Therefore, many ateliers already active in Campania began to produce also local imitations of ACW. Finally, in order to better understand the organization of these ateliers in the region, the present study provides a detailed map that shows the distribution of both the producer and consumer sites, suggesting also the existence of other ateliers in Vesuvian area and in Hirpinia.